E tem choro no Maranhão? Subsídios históricos e musicológicos para um processo de formação do choro no Maranhão entre o final do séc. XIX e meados do séc. XX. - Raimundo João Matos Costa Neto (2015)
This thesis proposes a discussion about one formation process of choro music in the state of Maranhão (Brazil) at the end of the 19th and the beginning of the 20th century. In the historic bibliography about the popular Brazilian music there is only a modicum of references about the music produced in the state. This paper shows that some of the musical activities, specially the ones influenced by European music, had their beginnings during the founding of the capital, São Luís, in 1612. According to the literature that deals with the inception of the choro music, this genre had its only origin traced back entirely to the city of Rio de Janeiro at the end of the 19th century. These works had their onset in the music that came from Europe, like waltz, polka, mazurka, schottische and a Brazilian twist to these music styles. Based on information extracted from texts about the history of music in Maranhão, in diverse literary works and the analysis of musical sheet found in the João Mohana Archives, the author compares the scenarios from Rio de Janeiro and Maranhão from this period. The author does this to identify analog characteristics in order to prove that the choro genre in Maranhão had parallel origins with that of Rio de Janeiro. The editing of 14 (fourteen) unpublished works from the choro repertory helped to preserve the historical musical heritage of this state and brought to light previously undiscovered musical pieces, musicians and composers.